Evidence Jury Impeachment - Miller, Colin (Open textbook library., 2014)
The anti-jury impeachment rule, contained in Federal Rule of Evidence 606(b) and state counterparts, is a rule preventing the admission of jury testimony or statements in connection with an inquiry into the validity of the verdict, subject to certain exceptions. Through a series of cases and hypotheticals drawn from actual cases, this chapter gives readers a roadmap for how to address any jury impeachment issue in practice. Faculty materials also available: In addition to the free, open learning materials for students listed above, this eLangdell chapter includes a teacher's manual. Faculty and staff at CALI member schools can access these materials by logging in to eLangdell with a cali.org username and password. Contact CALI if you have questions.